Association between Blood Lead Levels and Heme Synthesis Process in Paint Industry Workers - Sharnella Janet Yapfrine; Katharina Oginawati; Sonia Buftheim; Yuyun Ismawati (Eduvest - Journal of Universal Studies, 2023)
Lead is a heavy metal that can pose various health risks to humans. One of the effects of lead exposure is the inhibition of the delta-ALAD enzyme which plays a role in the heme synthesis process. Blood lead levels and delta-aminolevulinic acid dehydratase (ALAD) activity are considered biomarkers of lead exposure and lead toxicity respectively. The inhibition of ALAD can cause in accumulation of ALA in urine and also inhibit the heme synthesis pathway that plays a role in hemoglobin production. The present study was designed to investigate the association between the BLLs and the heme synthesis process, which is detected by the accumulation of urinary ALA (ALA-U) and decreasing hemoglobin, in paint industry workers from Indonesia. A total of 52 paint industry workers participated in this study. Blood lead was measured using ICP-MS and ALA-U was measured using spectrophotometer method. Mean blood lead was 4.213±1.6 mg/L; and 17 workers (32.7%) crossed the recommended level of 5 mg/L. Mean urinary ALA level was 3.712±2.5 mg/L; and 11 workers (11.54%) crossed the normal level of 6 mg/L but still classified as acceptable. Mean hemoglobin level was 15.273±1.03 g/L. The correlation between the BLL and ALA-U was found to be positive but not significant. Meanwhile, the correlation between the ALA-U and the hemoglobin levels was found to be negative but also not significant.